Characterization and Dynamics of Intracellular Gene Transfer in Plastid Genomes of Viola (Violaceae) and Order Malpighiales - Yang, JiYoung; Park, Seongjun; Gil, Hee-Young; Pak, Jae-Hong; Kim, Seung-Chul (Frontiers in Plant Science, 2021)
Functional gene transfer from organelles to the nucleus, known as intracellular gene transfer (IGT), is an ongoing process in flowering plants. The complete plastid genomes (plastomes) of two Ulleung island endemic violets, Viola ulleungdoensis and V. woosanensis, were characterized, revealing a lack of the plastid-encoded infA, rpl32, and rps16 genes. In addition, functional replacement of the three plastid-encoded genes in the nucleus was confirmed within the genus Viola and the order Malpighiales. Three strategies for the acquisition of a novel transit peptide for successful IGT were identified in the genus Viola. Nuclear INFA acquired a novel transit peptide with very low identity between these proteins, whereas the nuclear RPL32 gene acquired an existing transit peptide via fusion with the nuclear-encoded plastid-targeted SOD gene (Cu-Zn superoxide dismutase superfamily) as one exon, and translated both proteins in the cytosol using alternative mRNA splicing. Nuclear RPS16 contains an internal transit peptide without an N-terminal extension. Gene loss or pseudogenization of the plastid-borne rpl32 and rps16 loci was inferred to occur in the common ancestor of the genus Viola based on an infrageneric phylogenetic framework in Korea. Although infA was lost in the common ancestor of the order Malpighiales, the rpl32 and rps16 genes were lost multiple times independently within the order. Our current study sheds additional light on plastid genome composition and IGT mechanisms in the violet genus as well as in the order Malpighiales.